1985
DOI: 10.1016/s0022-5347(17)46962-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Calcium Nephrolithiasis with Potassium Citrate

Abstract: The long-term effects of potassium citrate therapy (usually 20 mEq. 3 times daily during 1 to 4.33 years) were examined in 89 patients with hypocitraturic calcium nephrolithiasis or uric acid lithiasis, with or without calcium nephrolithiasis. Hypocitraturia caused by renal tubular acidosis or chronic diarrheal syndrome was associated with other metabolic abnormalities, such as hypercalciuria or hyperuricosuria, or occurred alone. Potassium citrate therapy caused a sustained increase in urinary pH and potassiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
1
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(76 citation statements)
references
References 23 publications
3
70
1
2
Order By: Relevance
“…In the course of our two trials we observed recurrent stones in only 1 patient. This fact confirms the effective ness of alkali citrates for stone prophylaxis as previously demonstrated in long-term trials [9][10][11]. This form of therapy appears to be more effective and better tolerated than other approaches to metaphylaxis (e.g.…”
Section: Resultssupporting
confidence: 86%
“…In the course of our two trials we observed recurrent stones in only 1 patient. This fact confirms the effective ness of alkali citrates for stone prophylaxis as previously demonstrated in long-term trials [9][10][11]. This form of therapy appears to be more effective and better tolerated than other approaches to metaphylaxis (e.g.…”
Section: Resultssupporting
confidence: 86%
“…The relationship between hypocitraturia and urinary stone formation is well known in distal renal tubular acidosis, chronic diarrheal diseases, urinary tract infection, and in renal insufficiency, but is not clear in idiopathic pediatric Ca-Ox urinary stone disease [23,24]. Under normal conditions, citrate is freely filtered at the glomerulus with a 65-90% reabsorption rate, with almost no secretion by the tubulus [25].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of citrate on calcium oxalate crystal growth and aggregation is also linked to a direct effect on the crystal surface (3,10). Consequently, and because of lack of significant adverse effects, citrate preparations are widely used in subjects with calcium oxalate nephrolithiasis (2,(11)(12)(13).…”
mentioning
confidence: 99%